Study of In-Cylinder Heat Transfer Boundary Conditions for Diesel Engines Under Variable Altitudes Based on the CHT Model - Zhang, Yu; Yan, Yuchao; Yang, Ruomiao; Wang, Qifan; Zhang, Bowen; Gan, Qingliang; Liu, Zhentao; Fu, Jiahong (Frontiers in Energy Research, 2022)
The reliability of combustion chamber components is mainly determined by the thermal load of diesel engines. Under the plateau operation condition, diesel engine performance degradation and ablation area appear. Therefore, it is crucial to study the engine heat transfer phenomenon at different altitudes, of which the Woschni formula cannot meet the accuracy requirement. With the motive of modifying and calibrating the Woschni formula at different altitudes, a modified conjugate heat transfer (CHT) model of the combustion chamber and the cooling medium was proposed to analyze the temperature distribution of the cylinder head. The results indicated that relative errors were controlled within 5% under variant altitudes, comparing the temperature field of the numerical simulation with the single-cylinder engine experiment test data. Therefore, the modified in-cylinder conjugate heat transfer model can be used to predict the thermal load of diesel engine combustion chamber components under different altitude operating conditions.